1999
DOI: 10.1017/s135561779956606x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 7- to 95-year-old individuals in a Chinese version of the category fluency test

Abstract: A version of the category fluency test including the categories of animal and transportation, was administered to 316 Chinese native speakers ranging in age from 7 to 95. Results indicated that the number of items generated in the category fluency test increases with age from childhood to adulthood with a peak performance in adults aged from 19 to 30, and then declines subsequently into late life. All participants, regardless of their age, generated more animal than transportation names. Educational le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 63 publications
6
60
1
1
Order By: Relevance
“…Nevertheless, we failed to find a gender effect, as did our previous survey (24). Other studies have not found a gender effect, especially when results by gender were corrected for educational level (29).…”
Section: Discussioncontrasting
confidence: 86%
“…Nevertheless, we failed to find a gender effect, as did our previous survey (24). Other studies have not found a gender effect, especially when results by gender were corrected for educational level (29).…”
Section: Discussioncontrasting
confidence: 86%
“…The frontal lobe undergoes substantial shrinkage with age relative to other regions [23] and decreased frontal function has been associated with normal aging on neuropsychological tests [24,25] . Category fluency decreases with healthy aging [26,27] , possibly due to its frontal component [27] . One intriguing possibility to explain the findings of intact categorical clustering into old age [16,18,19] is that perhaps the emphasis on categorization throughout one's life in Western society protects the strategy against age-related declines.…”
Section: Introductionmentioning
confidence: 99%
“…Verbal fluency tasks are commonly used in neuropsychological assessment, since they are easy to administer (Carnero, Lendínez, Maestre, & Zunzunegui, 1999;Kempler, Teng, Dick, Taussig, & Davis, 1998), sensitive to brain damage and cognitive deterioration (Acevedo et al, 2000;Bruyer & Tuyumbu, 1980;Carnero et al, 1999;Chan & Poon, 1999;Joanette & Goulet, 1986;Kempler et al, 1998;Ratcliff et al, 1998;Rosen, 1980;Ruff, Light, Parker, & Levin, 1997;Stuss et al, 1998;Tombaugh, Kozak, & Rees, 1999;Troyer, Moscovitch, Winocur, Alexander, & Stuss, 1998) and can be applied to different cultural groups (Kempler et al, 1998). Verbal fluency tasks have also been applied in the investigation of illiterate and other low-level educational groups because they do not require reading or writing skills.…”
Section: Introductionmentioning
confidence: 99%